2005
DOI: 10.1055/s-2005-870323
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Induced by Pharmacological Activation of Central Serotonergic Pathways Depends on the Functional Integrity of Brain CRH System and 5-HT3 Receptors

Abstract: In the present study, we investigated the effect of central serotonergic pathway activation achieved through third ventricle injections of quipazine, a serotonergic agonist, on plasma glucose levels of fasted and fed adult Wistar male rats, whose third ventricles were canulated 7 days before the experiments. Central quipazine administration induced a significant increase in plasma glucose levels in fasted animals, but was unable to modify plasma glucose concentrations in fed rats. Pretreatment with alpha-helic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Few clinical studies also employed 5-HT 3 receptor antagonists in several neuropsychiatric disorders (Israili, 2001;Wolf, 2000;McCann et al, 1997). Interstingly, 5-HT 3 receptor antagonists like ondansetron, LY-278584 and tropisetron have shown to regulate the plasma glucose level in various assays (Carvalho et al, 2005;Heimes et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Few clinical studies also employed 5-HT 3 receptor antagonists in several neuropsychiatric disorders (Israili, 2001;Wolf, 2000;McCann et al, 1997). Interstingly, 5-HT 3 receptor antagonists like ondansetron, LY-278584 and tropisetron have shown to regulate the plasma glucose level in various assays (Carvalho et al, 2005;Heimes et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether ondansetron alone can affect the plasma glucose levels in Mandhane et al's (2012) study. Another study showed that pretreatment with ondansetron was able to reduce the hyperglycemic response induced by central administration of quipazine; however, ondansetron injection alone into the third ventricle had no effect on plasma glucose concentrations in rodents (Carvalho et al, 2005). There have been no reports showing any effect of ondansetron on blood glucose levels in humans.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the fact that adrenodemedullation prevented both the glucose rise and the insulin fall, but not the glucagon rise, indicated that the effects at the beta-cell level were mediated by the adrenaline released from the adrenal glands [21,29,31,33,34,37,38].…”
Section: Peripheral Mechanismsmentioning
confidence: 99%
“…In addition to the above and taking into account that plasma serotonin excites both alpha-cells and adrenal glands directly [21,29,[31][32][33][34], the disappearance of those hyperglycemic factors would favor the predominance of the insulinogenic effect registered in this study. This phenomenon should be associated with other findings showing that adrenalectomy is able to interfere with the glucagon induced plasma glucose rises provoked by intravenous administration of 5-HT [35].…”
Section: Peripheral Mechanismsmentioning
confidence: 99%